The Effect of 3.6 Million Refugees on Crime - Murat G. Kirdar; Iván G. López Cruz; Betül Türküm (Institute of Labor Economics (IZA), 2021)
Most studies examining the impact of migrants on crime rates in hosting populations are in the context of economic migrants in developed countries. However, we know much less about the crime impact of refugees in low- and middle-income countries—whose numbers are increasing worldwide. This study examines this issue in the context of the largest refugee group in any country—Syrian refugees in Turkey. Although these refugees are much poorer than the local population, have limited access to formal employment, and face partial mobility restrictions, we find that total crime per person (including natives and refugees) falls due to the arrival of the refugees. This finding also applies to several types of crime; the only exception is smuggling, which increases due to the population influx. We also show that the fall in crime does not result from tighter security; we find no evidence of a change in the number of armed forces (military and civil personnel) in the migrant-hosting regions.
Keywords: J15; K42; D74; 330; refugees; crime; security; immigration-crime nexus; civil war